Desenvolvimento de um sensor fotoeletroquímico para a detecção de Levodopa explorando uma plataforma à base de Titanato de Bário e Oxi-iodeto de Bismuto - BORGES, Bianca Ferreira (2024)
This work is based on the development of a photoelectrochemical sensor for the determination of levodopa. Initially, it was evaluated a photoelectrochemical system based on a three electrodes electrochemical system exploiting barium titanate sensitized with bismuth oxi-iodide (BiOI /BaTiO3/FTO) as the working electrode, Ag/AgCl in saturated KCl as the reference electrode, and Au as the counter electrode. Posteriorly, a self-powered photoelectrochemical system using the BiOI/BaTiO3/FTO platform as the photoanode and a copper oxide modified FTO eletrode (Cu2O/FTO) as the photocathode was investigated. X-ray diffraction of BiOI/BaTiO3 was carried out in order to assess the composition of the phases and the structure of the composite. Under optimised conditions, the photoelectrochemical sensor showed a wide linear range, with 4.98-38.5 μmol L-1 and recovery values of 98.74% and 98.28% for levodopa and a linear response range between 9.9-38.5 μmol L-1 for the self-powered photoelectrochemical sensor with recovery of 78.79% and 78.18% for levodopa. The photoelectrochemical system showed good selectivity against the some interferents normally found in the tested sample.